Evolution of brain size in class-based societies of fungus-growing ants (Attini) (2012)
A social lifestyle is often assumed to be more complex than a solitary one, due to social demands that may require increased cognitive capabilities. These nested assumptions underlie hypotheses to explain a correlation between brain size and group size in social vertebrates, using group size and accumulation of social traits, as alternative proxies for social complexity. Eusocial insects challenge the generality of the hypothesis that social complexity relies on increased cognitive capabilities of individuals. We used data from previously published studies to test for an association between sociality and brain size across 18 species (nine genera) of fungus-growing ants (Attini), which range from basal taxa with fewer than 100 monomorphic individuals, to derived colonies containing several million polymorphic, highly specialized individuals. Among monomorphic species, increased colony size was associated with decreased relative brain size and increased olfactory lobe size, although the latter result was sensitive to both the exclusion of potential outliers and whether phylogenetically independent contrasts were used. Within leafcutters (Atta), the relative size of the antennal lobes was also associated with group size, but may also reflect ecological foraging specialization, which may be a confounding variable. Comparisons between class- and individual-based societies highlight the general problem of increasing social structure in proportion to group size and show that there are alternative solutions to this problem: one alternative involves increasing behavioural specialization of individuals and evolved rules; the other involves increased diversification of individual behaviour, social norms and ultimately institutions.